Modern Diagnostics of Nerve Regeneration after Surgery - Komil qizi, Ganjiyeva Munisa; Olim o'g'li, Mustafayev Muxammadjon (American Journal of Bioscience and Clinical Integrity, 2025)
A fundamentally new approach in experimental neurohistology can be called tubulation using conductors - tubes, which serve as a substrate for the growth of nerve fibers through the site of injury of the nerve trunk [25, 26]. In conditions of diastasis, such a substrate can also be a reservoir for a filler that stimulates regeneration processes. In addition, the conductor prevents the penetration of surrounding connective tissue into the site of injury, which limits the formation of a connective tissue scar that prevents the passage of growing nerve processes to the distal tail [21, 27].